2014
DOI: 10.14260/jemds/2014/3289
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Haemodynamic Response to Laryngoscopy and Endotracheal Intubation Using Intra-Oral Ivabradine: A Clinical Study

Abstract: BACKGROUND AND OBJECTIVES: Rapid and dramatic hemodynamic changes which adversely affect the patient may occur during laryngoscopy and intubation. The present study evaluates the effect of oral ivabradine on the hemodynamics during laryngoscopy and endotracheal intubation in patients undergoing surgical procedures under general anesthesia. METHODS: A prospective randomized, single blinded study was conducted in 50 ASA-I adult patients undergoing various procedures under general anesthesia. The patients were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This aspect of ivabradine has been explored in some recent studies and excellent results have been obtained. 5,[11][12][13] The dose of ivabradine (2.5 mg) used in our study gave a controlled field and did not cause any sudden drop-in HR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This aspect of ivabradine has been explored in some recent studies and excellent results have been obtained. 5,[11][12][13] The dose of ivabradine (2.5 mg) used in our study gave a controlled field and did not cause any sudden drop-in HR.…”
Section: Discussionmentioning
confidence: 99%
“…"If " blockade results in a decrease in the slope of spontaneous depolarization, leading to an increase in the time interval between successive action potentials in the SA node, thus decreasing the HR. 5 Ivabradine decreases the HR without any inordinate change in hemodynamics of unhealthy, compromised patients. The drug can be used both in hypertensive and normotensive patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflex cardiovascular effects of laryngoscopy and intubation in anesthetized patients have been described previously. [8] These reflex changes which include the rise in arterial pressure (SBP, DBP, MBP) and heart rate are at their peak approximately 30-45 sec after laryngoscopy.Attempts to attenuate these responses by various drugs or techniques or their combinations have met with varying success. In this study, both the study group and control group cases received the same pre-medications.…”
Section: Discussionmentioning
confidence: 99%
“…Raghuram et al [29] evaluated the efficacy of oral ivabradine to attenuate the hemodynamic responses after intubation. They found that ivabradine is an extremely useful drug to prevent abnormal increase in heart rate and blood pressure to a lesser extent seen during laryngoscopy and endotracheal intubation and recommended its routine use in all patients at risk for hypertension and tachycardia during laryngoscopy and endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%